2014
DOI: 10.1016/j.adhoc.2011.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Data transmission and base-station placement for optimizing the lifetime of wireless sensor networks

Abstract: We study the problem of transmitting data from a set of sensors to a base-station where the data is to be gathered. Each sensor continuously generates data and has to transmit it through the network (via other sensor nodes) to the basestation. Considering the battery limitations of the sensors, our goal is to find an optimum location of the base-station and a corresponding data transmission scheme for routing the data from the sensors, such that the network is operating for the longest possible time. We focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…1 is a continuous VOLUME 3, 2015 function in (0, D], then there must be one d hop ∈ (0, D], which achieves minimum value in (24). As a result, the optimal d hop is existed if the following equation is proved.…”
Section: Optimizing Design a Single-source Linear Networkmentioning
confidence: 93%
“…1 is a continuous VOLUME 3, 2015 function in (0, D], then there must be one d hop ∈ (0, D], which achieves minimum value in (24). As a result, the optimal d hop is existed if the following equation is proved.…”
Section: Optimizing Design a Single-source Linear Networkmentioning
confidence: 93%
“…In the context of sensor networks, several studies have considered the optimal node placement schemes which are always NP-hard. To tackle such complexity, several heuristics have been proposed to find sub-optimal solutions [5,6] in presence of stationary nodes. In VANETs and mesh networks, there are several studies on roadside units (RSUs) placement problem.…”
Section: Related Workmentioning
confidence: 99%
“…In 2014, Arkin et al [1] focused on shallow tree topologies to maximize the network lifetime for energy efficiency on wireless sensor network optimization problem. However, Chanak et al [3] identified an issue in WSN for analyzing the network due to improvisational nature.…”
Section: Related Workmentioning
confidence: 99%
“…Their review outcomes are summarized in Table 1. The LEACH method used in [1] has advantages such as scalability and increased network lifetime. Nevertheless, it does not have inter-cluster communication.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation